Development Strategy for Arabic Coffee Processing Business in Kreasi Kopi Medan - Simatupang, Donny Ivan Samuel; Pakpahan, Helena Tatcher; Panggabean, Lamris (ITScience (Information Technology and Science), 2024)
Various strategies and innovations are implemented as steps to achieve the desired profits and goals. However, it is also necessary to maintain business continuity for a long time and expand the business so that the wheels of the business continue to run smoothly. This research aims to analyse internal and external company factors that influence the development of Arabica coffee processing businesses in the research area, to analyse development strategies and alternative strategies for developing Arabica coffee processing businesses. The data analysis method was carried out using descriptive qualitative and using a SWOT analysis diagram. The results of this research are internal factors of strength, namely: initial business capital, attractive business name, place design, affordable prices, quality raw materials, varied menu variants, taste of coffee drinks and payment methods. Internal factors of weakness are: less strategic business location, limited workforce, service, product visuals, parking facilities and product variants that are not durable. External factors of opportunity are: consumer image, use of technology, consumers buying consistently, changes in consumer tastes, consumers buying online, adding menu variants and social media as promotion. External threat factors are: similar competitors, similar products, the existence of substitute drinks, fluctuations in raw material prices and declining consumer interest. Based on the SWOT analysis diagram, it is known that the company's position is in quadrant 1, supporting an aggressive strategy.